PENERAPAN STRATEGI PEMBELAJARAN FIQIH BERBASIS AKTIF DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Mantazli; Andi Warisno; Mustaqim Hasan; Suci Hartati (UNISAN JURNAL, 2022)
The purpose of this study was to determine how to apply strategies in Fiqh learning at MTs Hidayatul Mubtadiin. How are the Constraints to Implementing Strategy in Fiqh Learning at MTs Hidayatul Mubtadiin. The type of research used in this research is descriptive qualitative to obtain a complete and in-depth description. The key instrument is the researcher himself, and the data collection techniques used are observation, interviews and documentation. The data is analyzed by reducing the data, presenting the data and drawing conclusions. The results of the study show that: The application of learning strategies greatly facilitates the teacher of fiqh lessons in conveying theory in the classroom with many strategies that are used and applied easily. Several obstacles are influenced by internal and external factors which are quite difficult for learning activities but can be overcome with several strategies and shortcuts by using the right strategy to be conveyed by the subject teacher.